On the Sensitivity of Electron-Injection Detectors at Low Light Level - Vala Fathipour; Iman Hassani Nia; Alireza Bonakdar; Hooman Mohseni (IEEE Photonics Journal, 2016)
We present the signal-to-noise performance of a short-wave infrared detector, which offers an internal avalanche-free gain. The detector is based on a similar mechanism as the heterojunction phototransistor and takes advantage of a type-II band alignment. Current devices demonstrate a noise-equivalent sensitivity of ∼670 photons at 260 K and over a linear dynamic range of 20 dB. While this level of sensitivity is about an order of magnitude better than an ideal p-i-n detector attached to the same low-noise amplifier, it was still limited by the amplifier noise (∼2600 electrons root mean square) due to the insufficient device gain. Performance comparison with other SWIR detector technologies demonstrates that the so-called electron-injection detectors offer more than three orders of magnitude better noise-equivalent sensitivity compared with state-of-the-art phototransistors operating at similar temperature.